An English-Malay translation memory system - Ab. Rahman, Suhaimi; Abdul Aziz, Normaziah; Solemon, Badariah (2008)
This paper discusses on an English-Malay Translation Memory (TM) prototype system developed as a tool to translate English to Malay text by re-using pre-translated examples stored in the TM repositories. The architectural system design and structural model of the English-Malay TM using Data Flow Diagrams (DFDs) are also described. We then shared the sample of implementation model of the English-Malay TM system that will be evaluated by a group of free-lance translators. Plans of further work are also listed in concluding this paper.